Investigating the determinants of international differences in the prevalence of chronic widespread pain: evidence from the European Male Ageing Study. Issue 5 (24th July 2008) - Macfarlane, G J; Pye, S R; Finn, J D; Wu, F C W; Silman, A J; Bartfai, G; Boonen, S; Casanueva, F; Forti, G; Giwercman, A; Han, T S; Huhtaniemi, I T; et al.
Abstract : Objectives: To determine whether among middle-aged and elderly men there is evidence of international differences in the prevalence of chronic widespread pain (CWP) and whether any such differences could be explained by psychological, psychosocial factors or differences in physical health status. Methods: The European Male Ageing Study (EMAS) sampled from population registers in cities (centres) of eight European countries. Each centre recruited an age-stratified sample of men aged 40–79 years. Information on pain was collected by questionnaire and subjects were classified according to whether they satisfied the American College of Rheumatology definition of CWP. Information was collected on social status, mental health, recent life events and co-morbidities. Results: Across all centres 3963 subjects completed a study questionnaire, with participation rates ranging from 24% in Hungary to 72% in Estonia. There were significant differences in prevalence: between 5% and 7% in centres in Italy, England, Belgium and Sweden, 9–15% in centres in Spain, Poland and Hungary and 15% in Estonia. There were strong relationships between poor mental health, adverse recent life events, co-morbidities and CWP. Adjustment for these factors explained between half and all of the excess risk in the eastern European centres: the excess risk in Poland was explained (odds ratio (OR) 1.1, 95% CI 0.9 to 1.2) but there remained excess risk in Hungary (OR 1.6, 95% CI 1.4 to 1.8) and Estonia (OR 2.6, 95% CI 2.2 to 2.9). Conclusions: This study is the first directly to compare the occurrence of CWP internationally. There is an excess prevalence in countries of eastern Europe and this excess is associated with adverse psychosocial factors as well as poorer psychological and physical health.